2020
DOI: 10.1038/s41541-020-00221-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the immunogenicity of prime-boost vaccination with the replication-deficient viral vectored COVID-19 vaccine candidate ChAdOx1 nCoV-19

Abstract: Clinical development of the COVID-19 vaccine candidate ChAdOx1 nCoV-19, a replication-deficient simian adenoviral vector expressing the full-length SARS-CoV-2 spike (S) protein was initiated in April 2020 following non-human primate studies using a single immunisation. Here, we compared the immunogenicity of one or two doses of ChAdOx1 nCoV-19 in both mice and pigs. Whilst a single dose induced antigen-specific antibody and T cells responses, a booster immunisation enhanced antibody responses, particularly in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
122
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 25 publications
11
122
0
2
Order By: Relevance
“…These are typically based on another virus that has been engineered to express the S and has been disabled from replication in vivo by deletion of parts of its genome. The majority of these approaches are based on adenovirus (AdV) vectors but modified vaccinia Ankara, human parainfluenza virus vectors, influenza virus, andeno-associated virus (AAV) and Sendai virus are used as well ( Figure 3) 32,41, [45][46][47][48][49] . The majority of these vectors are delivered intramuscularly, enter the vaccinees' cells and then express the spike protein to which the host immune system responds.…”
Section: Replication Inactive Vectorsmentioning
confidence: 99%
“…These are typically based on another virus that has been engineered to express the S and has been disabled from replication in vivo by deletion of parts of its genome. The majority of these approaches are based on adenovirus (AdV) vectors but modified vaccinia Ankara, human parainfluenza virus vectors, influenza virus, andeno-associated virus (AAV) and Sendai virus are used as well ( Figure 3) 32,41, [45][46][47][48][49] . The majority of these vectors are delivered intramuscularly, enter the vaccinees' cells and then express the spike protein to which the host immune system responds.…”
Section: Replication Inactive Vectorsmentioning
confidence: 99%
“…Indeed to address the urgent need for a safe and e cacious vaccine against the SARS-CoV-2 several vibrant initiatives have been started as never before. For example, vaccine manufacturing front-runner come-up with mRNA vaccines [44], viral vector vaccine [45], classical attenuated vaccine etc. [46].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, specific IFN-γ secretion T cell response was prolonged at high level after boosting vaccination. Two recent publications compared prime only with a single-dose of ChAdOx1 nCoV-19 and homologous boost with a second dose of ChAdOx1 nCoV-19 vaccine in mice and pigs, and human clinical trials, showed that boost vaccination significantly increased and prolonged the level of binding or neutralizing antibody response to SARS-CoV-2 ( 11, 20 ). By boosting with Ad5-S vaccine the Ad26-S vaccine primed immunization, a higher level of immunity was observed in humans as reported in a recent Russian study ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, relatively weaker protection in animals and lower immune response in humans were observed with a single dose of vaccine compared with prime-boost immunizations by two or three doses of inactivated virus or mRNA vaccines ( 1519 ). Enhancement of immune response was evidenced by prime and boost vaccination regimens with homologous boosting of ChAdOx1 nCoV-19 in animals and humans ( 11, 20 ), or with heterologous Ad26 and Ad5 vectored COVID-19 vaccines in humans ( 21 ).…”
Section: Introductionmentioning
confidence: 99%